Green marketing mix and intention to purchase green cosmetic product: Mediating effect of self-efficacy / Mawaddah Mohamad - Mohamad, Mawaddah (2022)
As the concept of green cosmetic products emerged, customers began to exploit green cosmetics as they prioritise their health in avoiding the risk from the chemical products. Scholars argued that the adoption of green products is influenced by the green marketing concept. To understand up to what extend customers’ self-efficacy plays a role in connecting the Marketing Mix and purchase intention, this study aims to examine the mediating effect of consumer Self-efficacy on the relationship between Green Marketing Mix which consist of 4Ps elements; Green Product (GProduct), Green Price (GPrice), Green Place (GPlace), and Green Promotion (GPromo) and the intention to purchase Green Cosmetic Product (GCP). By employing the survey method, a total of 268 students from Universiti Utara Malaysia participated in this study. The results suggested that Self-efficacy mediates the relationship between GPrice, GPlace, GPromo on purchase intention. Through the Self-efficacy enhancement, the element of price, place and promotion were significantly affected by the purchase intention. Whilst, the relationship between GProduct and purchase intention is not mediated by Self-efficacy. Thus, this implies that even though customers believe the GCP are safe and have many benefits, it still could not increase their Self-efficacy which can continue with the purchasing. This study has expanded the Marketing Mix and Self-efficacy theory in the form of understanding the green elements that contribute to customers’ purchase intention.